The effect of intravenous adrenaline and noradrenaline infusion of peripheral lymph flow in the sheep. - McHale, N G (1983)
Pressure fluctuations and lymph flow were measured in popliteal, prefemoral and mesenteric efferent lymphatic vessels in conscious sheep. Intravenous adrenaline infusion increased frequency of lymphatic contraction and lymph flow in all three vessels. In the case of the prefemoral vessels flow remained high after the infusion had stopped. Intravenous noradrenaline infusion also increased frequency of contraction and lymph flow in all three vessels but prefemoral flow was depressed after the infusion had stopped. Lymphatic frequency of contraction and lymph flow increased when the animals were started. Anaesthetizing the animals with pentobarbitone did not abolish lymphatic contractions, nor did it prevent the response to adrenaline and noradrenaline infusion. The most obvious interpretation of these results is that adrenaline and noradrenaline act by increasing frequency and force of pumping of lymphatic vessels.